2002
DOI: 10.1016/s0377-1237(02)80083-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc Levels in Cutaneous Disorders

Abstract: Senun zinc levels were studied in 7S patients or different cutaneous disorders and 24 healthy (ontrois. It was found to be significantly lower in acne vulgaris (715 ±215~gmIlOOml),leprosy(8S.9 ± 26.9f.1gm1lOOml) and psoriasis (93.3 ± 25.9J1g1l11100m1) as compared to healthy controls (105.3 ± 3O.1J.4PD1100m1). No significant correlation was found in other cutaneous disorders studied I.e. vitiligo and aphthous ulcers where serum zinc levels were found to be 97.3 ± 26.6 )J.gmIlOOml and 105.2 ± 23.S I!gmllOOml res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 10 publications
(5 reference statements)
5
29
1
2
Order By: Relevance
“…The results of this study are consistent with the findings of Arora et al ’ s study that confirmed the role of zinc deficiency   in certain diseases such as psoriasis, acne, vulgaris and leprosy [6]. Since lichen planus is a mucocutaneous disease and zinc has a substantial role in development of epithelium, ulceration in dermatologic diseases and simultaneous zinc deficiency in these diseases may endorse the role of this element on pathogenesis of lichen planus disease.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study are consistent with the findings of Arora et al ’ s study that confirmed the role of zinc deficiency   in certain diseases such as psoriasis, acne, vulgaris and leprosy [6]. Since lichen planus is a mucocutaneous disease and zinc has a substantial role in development of epithelium, ulceration in dermatologic diseases and simultaneous zinc deficiency in these diseases may endorse the role of this element on pathogenesis of lichen planus disease.…”
Section: Discussionsupporting
confidence: 92%
“…No significant alterations in the serum zinc levels were detected in cases of vitiligo and aphthous ulcers, compared to healthy individuals in the study of Arora et al [6]. It seems that the reason for this difference is the dissimilarity in type of involved autoimmune disease and the type of aphtus lesions (minor type) in their study which apparently could not influence the serum zinc level.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Serum Cu and Zn were compared between the control and vitiligo patients, with vitiligo patients having significantly lower serum levels of both Cu and Zn compared to controls [34]. Although both of these studies indicate some relationship between serum Zn levels and vitiligo, other findings have determined no significant difference between Zn levels in vitiligo patients compared to controls, leaving this topic controversial [37].…”
Section: Minerals: Zinc and Coppermentioning
confidence: 99%
“…Arora et al did not find any significant alteration in serum Zn levels in vitiligo patients [122]. On the other hand, in another study Helmy et al reported that serum Zn and Cu levels were significantly higher in active vitiligo patients secondary to their release from the peripheral blood mononuclear cells due to apoptosis [123].…”
Section: Vitiligomentioning
confidence: 99%